The presentations of family in comic books - ideological involvements - Gulanowski, Jacek (Karkonoska Państwowa Szkoła Wyższa, 2011)
Comics (despite its history dating back to the end of 19th century) is still a medium undervalued and underestimated. However, in comics one may discover role models important for the readers, who shape their own understanding of family, aims of family life or proper forms of its realization by accepting, negating or reinterpreting those role models. The aim of comics is the creation (within one piece) of a language understood by as many readers as possible. Popularity of comic books, specificity of its forms of expression and relatively low cost of “production” made possible attempts of the use of this for ideological goals since its very eginnings. Those attempts have been made by both groups at power as well as those who tried to resist their pressure. Ideological entanglement is not only observed in the case of comics consciously used for spreading a specific agenda. It also exists in comics, which, according to their authors, “only tell a story”.
Keywords: comics; family; ideology; popular culture; upbringing; manipulation; propaganda; education